Regdogs (2020)
From the moment the dogs became a member of the family the need has been generated to provide them with benefits such as health and beauty which it involves the use of paper for its registration, therefore, it does not help to conserve the environment. That is why we see the need to generate a device that contains the dog's magnetic information, in an easier way to manage using bluetooth technology and Arduino.